Evolution of Mechanization and Automation in Dairy Farming - Yu. A. Tsoy; V. V. Kirsanov; R. A. Mamedova; S. V. Kirsanov (Сельскохозяйственные машины и технологии)
The paper shows the development of technologies and tools of mechanization and automation in livestock farming for the period from 1930 to the present. (Research purpose) Given the cyclical nature of processes and the nuanced interpretations of scientific heritage, it is necessary to investigate the historical experience and contributions of scientists to the development and practical implementation of mechanization and automation tools in livestock farming. (Methods and materials) The paper examines the primary stages of mechanization and automation in cow milking, starting with the development of the first Soviet three-stroke milking machine DA-3. It considers the contributions made by specialized institutes of the All-Russian Academy of Agricultural Sciences and individual scientists in formulating testing methodologies for milking machines. Additionally, it explores the development and adoption of novel electromechanical tools for dairy farms. (Results and discussion) Considered in this paper are the pioneering eﬀorts in the creation of the first milking parlors. These include the stationary herringbone type machines with a parallel-pass design, spearheaded by V.S. Krasnov, V.F. Korolev, V.P. Larin, V.P. Pokhvalensky, and A.N. Dormidontov, and the development of mobile carousel parlors of the «rotating herringbone» type, engineered by the design bureau of the Siberian Research Institute of Agriculture under the supervision of I.I. Teslenko, N.V. Krasnoshchekov, K.S. Shapovalov, N.K. Vazenmiller, A.V. Goldenfang. (Conclusions) The paper notes the significance of adopting a systematic approach to the developing of machinery for livestock farming mechanization. This approach was actively pursued by N.M. Morozov, the member of the Russian Academy of Sciences. A significant milestone in the advancement of the theory and practice of animal husbandry processes was the pioneering work in developing and implementing technology for flow-conveyor animal service, headed by Member of the Russian Academy of Sciences L.P. Kormanovsky. The paper reveals the necessity of conducting a historical practices from previous generations. This approach helps to develop modern models of machinery and equipment and avoid mere replication of foreign designs. It also facilitates independent research and development eﬀorts, incorporating insights from the accumulated experience of utilizing equipment and technologies in Russia.